Korelasi Kompetensi dan Keprofesionalan Guru dalam Proses Pembelajaran di Gresik: Correlation of Competence and Teacher Professionalism in the Learning Process in Gresik - fina Ochtavia Ramadhani; Maluha Nabla (Fakultas Adab dan Bahasa UIN Raden Mas Said Surakarta, 2025)
In the effort to improve the overall quality of education, especially in Gresik Regency, reliable human resources are needed, namely professional teachers or educators. Professional teachers are supported by several underlying factors, such as teacher competence and the professional components of teachers. Teacher competence includes four aspects, namely pedagogical, professional, personal, and social competence. This study aims to determine and describe the correlation between teacher competence and teacher professionalism in the learning process in Gresik. This research uses a qualitative method with a descriptive approach. The data sources were obtained from interviews with elementary school teachers, junior high school teachers, and senior high school teachers who have at least five years of teaching experience in Gresik. The data analysis technique used by the researcher is the interactive technique of Miles and Huberman, which includes data reduction, data presentation, and conclusion. The results of this study show a mutually reinforcing relationship between teacher competence and professionalism. Teachers who possess mastery of four competencies tend to exhibit professional behavior such as being a resource for learning, manager, facilitator, motivator, demonstrator, mentor, and continuously evaluating learning and teaching success. Therefore, mastery and strengthening of teacher competencies directly contribute to the enhancement of teacher professionalism in the learning process.